2022
DOI: 10.1590/1678-4324-2022200776
|View full text |Cite
|
Sign up to set email alerts
|

Flour of Winged-stem Passion Fruit Peel: Nutritional Composition, Incorporation in Cookies, and Sensory Acceptability

Raquel Flôres Sampaio,
Viviane da Cruz Lima,
Giselle Aparecida Marques Bungart
et al.

Abstract: The development of new products by adding value to residues such as passion fruit peel, which may contribute to additional nutritional value, is of great interest. Thus, the objective of this study was to characterize the flour of winged-stem passion fruit peel and use it in the preparation of cookies, along with the evaluation of its nutritional quality and sensory acceptability. Flavedo and albedo flours were produced from the winged-stem passion fruit, and 6 biscuit formulations were made, one standard and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…Much research has targeted the use of fruit peel in the development of products, since they have an interesting nutritional composition, with significant amounts of fibres, minerals and bioactive compounds (Brandão et al, 2020;Cunha et al, 2020;Damasceno et al, 2018). The breads developed in the present study presented sensory acceptability equal to or greater than that found in other studies with the addition of fruit peel flours in breads, including gluten-free breads prepared with tangerine peel flour (Lima et al, 2021) and breads with mixed seed flour and papaya peel (Santos et al, 2018), as well as the sweet PF in cookies (Sampaio et al, 2022), confirming that sweet PF can be used in bakery products.…”
Section: Sensory Analysissupporting
confidence: 49%
See 3 more Smart Citations
“…Much research has targeted the use of fruit peel in the development of products, since they have an interesting nutritional composition, with significant amounts of fibres, minerals and bioactive compounds (Brandão et al, 2020;Cunha et al, 2020;Damasceno et al, 2018). The breads developed in the present study presented sensory acceptability equal to or greater than that found in other studies with the addition of fruit peel flours in breads, including gluten-free breads prepared with tangerine peel flour (Lima et al, 2021) and breads with mixed seed flour and papaya peel (Santos et al, 2018), as well as the sweet PF in cookies (Sampaio et al, 2022), confirming that sweet PF can be used in bakery products.…”
Section: Sensory Analysissupporting
confidence: 49%
“…They were then cut into small pieces, distributed in trays lined with parchment paper and placed in a drying oven at 60 °C for 24 hours. After milling using a domestic blender of the brand Philips-Walita, the cut peel was sieved using 28 mm mesh sieves to obtain the flour (Figure 1), which was then stored in polyethylene bags at room temperature and under light (Sampaio et al, 2022).…”
Section: Production Of Sweet Passion Fruit Peel Flourmentioning
confidence: 99%
See 2 more Smart Citations
“…Organic residues that would generally be discarded can be used to nutritionally enrich food (Sampaio et al, 2022;Santos & André, 2021), as already observed in the use of flour from sweet passion fruit peel flour in sheep meat products (Maia, 2017) with increased fiber and minerals (Borges et al, 2020;Vasconcellos et al, 2001). The benefits also extend to its way of acting in the human body, being rich in antioxidants and presenting anti-inflammatory effect, which reduces the risk of inflammatory diseases and even cancer (Ozarowski et al, 2018;Wasicky et al, 2015).…”
Section: Introductionmentioning
confidence: 90%